2009
DOI: 10.1099/mic.0.032763-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Dicer-dependent RNA interference in the industrial penicillin producer Penicillium chrysogenum

Abstract: RNA interference (RNAi) is a sequence-specific post-transcriptional gene silencing system that downregulates target gene expression. Here, we provide several lines of evidence for RNA silencing in the industrial β-lactam antibiotic producer Penicillium chrysogenum using the DsRed reporter gene under the control of the constitutive trpC promoter or the inducible xylP promoter. The functional RNAi system was verified by detection of siRNAs that hybridized exclusively with gene-specific 32P-labelled RNA probes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…S2 in the supplemental material). Together with the previously described ⌬PclaeA mutant (26,33), five mutants lacking single genes for components of the velvet complex were available for our genetic study. Note that our genetic analysis was extended by the construction of four double-knockout strains, using single knockouts as a reference, and the corresponding genealogy of all strains is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S2 in the supplemental material). Together with the previously described ⌬PclaeA mutant (26,33), five mutants lacking single genes for components of the velvet complex were available for our genetic study. Note that our genetic analysis was extended by the construction of four double-knockout strains, using single knockouts as a reference, and the corresponding genealogy of all strains is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The marker-free ⌬Pcku70 strain served as a recipient for the construction of knockout mutants (32). In addition to newly generated deletion strains, the recently described ⌬PclaeA and ⌬PclaeA ⌬PcvelA strains were used for functional characterization (33). All P. chrysogenum strains were grown either in liquid complex medium (CCM) or minimal medium (MM) at 27°C and 120 rpm or on solid medium as already described (33).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The special collection of research papers found in this issue spans a range of topics and organisms. Topics covered include primary metabolism (Heyland et al, 2009;Domin et al, 2009;Dawe et al, 2009) and its regulation (Teves et al, 2009;Vongsangnak et al, 2009;Wong et al, 2009), as well as the cellular and systems biology of key processes that underlie fungal growth (Bormann & Tudzynski, 2009;Hutchison et al, 2009;Etxebeste et al, 2009;Janus et al, 2009;Eisenman et al, 2009;Gale et al, 2009;Avanzo et al, 2009;Mukaiyama et al, 2009;Zara et al, 2009). Organisms include well-known model systems (Saccharomyces cerevisiae, Schizosaccharomyces pombe, Neurospora crassa, Aspergillus nidulans), human pathogens (Candida albicans, Cryptococcus neoformans), plant pathogens (Claviceps purpurea, Cryphonectria parasitica, Fusarium solani) and industrial producers (Penicllium chrysogenum).…”
mentioning
confidence: 99%